Development of a Laboratory Size Single Toggle Jaw Crusher for Artisanal Miners and Stone Workers - Okechukwu, C.; Dahunsi, O. A.; Oke, P. K.; Oladele, I. O.; Dauda, M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
Comminution of minerals and stones in Nigeria is laden with myriads of resource challenges associated with other developing nations. A typical challenge is the need to import costly mining and mineral processing machineries or replace their components. To address this challenge, economic consideration was prominent in the development of components for the single toggle jaw crusher. Geometric modeling and structural/stress analysis of the components were achieved using Pro/Engineer® and Autodesk Inventor® computer applications. Designed eccentricity of 7 mm resulted in 5 mm throw and 0.01° angle of twist in the eccentric shaft. The designed base frame was statically stable, having yielded a maximum displacement of 0.008066 mm. Analysis of the compression spring indicated design compliance. Also, hardfaced crusher jaws and large diameter pulley and flywheel were developed. Selection of a three-phase, 3730 W electric motor resulted in a 0.24 ton/hr capacity jaw crusher in service. Optimal and maximum feed of the crusher were found to be 0.5 kg and 1 kg, respectively. Average eccentric shaft speed decreased with increased mass of granite lumps undergoing crushing. Therefore, the methods presented can be adopted in developing affordable and easily maintainable jaw crushers for artisanal miners and stone workers in Nigeria.